Staining Intensity of P16INK4a and Ki-67 Determine the Grade of Cervical Lesion: An Experience from Single Tertiary Care Centre - Sarma, Usha; Sarma, Purashree; Rabha, Dhanashri (Asian Pacific Journal of Cancer Biology, 2023)
Background: Various non-neoplastic and neoplastic lesions occur in cervix. HPV infection plays a major role in genesis of cervical lesions. Although most HPV infections are cleared out, infections with high risk HPVs may persist resulting in cervical dysplastic lesions. Using p16, a surrogate marker for HPV infection and Ki-67, a proliferation marker, along with histopathology, help improve the diagnostic accuracy of these lesions. The aim of the study was to evaluate the expression of p16 and Ki-67 in cervical lesions and association of their staining intensity with the histologic grading. Also to determine the predictive value of these markers in association with the cervical lesions. Methodology: A cross sectional study was carried out in 122 cases which were diagnosed histopathologically and then evaluated for the immunohistochemical expression of p16 and Ki-67 and their staining intensities. Results: The dysplastic lesions comprised of 83.7% cases [29.5% LSIL, 5.7% HSIL, 43.5% SCC and 4.9% adenocarcinoma] and 16.3% had non dysplastic lesions. p16 and Ki-67 expression were seen in 64.7% and 68% cases respectively. The intensity of p16 and Ki-67 expression was scored according to Galgano et al (2010). An increasing intensity of p16 and Ki-67 expression with higher grades of the cervical lesions was noted and this association was found to be statistically significant. (χ2 = 43.46 and p value < 0.0001). Conclusion: Though histopathology is the gold standard, the role of p16 and Ki-67 have emerged as useful adjuncts in detecting the true nature of the cervical lesions. They aid in the proper diagnosis, classification and distinction from non-dysplastic lesions, helping the clinicians in taking prompt action for management of the cases.